Isolation of Aerobic Bacterial Species Associated with Palpable Udder Defects in Non-Dairy Ewes - Mandefrot M. Zeleke; Paul R. Kenyon; Kate J. Flay; Danielle Aberdein; Sarah J. Pain; Niluka Velathanthiri; Anne L. Ridler (Animals, 2024)
The objectives of these studies were to identify associations between udder half defects (hard or lump) and bacteria isolated from milk or mammary tissue swabs, to compare with samples from normal udder halves at different physiological time points and to compare bacterial species isolated via milk and swabs of mammary tissue from within the same udder halves. A total of 1054 samples were aseptically collected from each udder half of 199 non-dairy breed (Romney) ewes from three different studies (Study A, n = 77; Study B, n = 74; and Study C, n = 48). Conventional bacterial culture and MALDI-ToF mass spectrometry were used for bacterial identification. Of the 225 samples from which bacteria were isolated, Mannheimia haemolytica and Streptococcus uberis were the dominantly identified species from defective udder halves, whereas coagulase-negative staphylococcus (CNS) species, mostly Staphylococcus simulans and Staphylococcus chromogenes, were more frequently isolated from normal udder halves. The ongoing presence of bacterial species over time was variable, although less frequently identified species showed less stability over time. A very high agreement (91.5%) of bacterial species identified was observed between the mammary tissue swab and udder half milk samples during post-weaning. In summary, palpable udder half defects were associated with bacterial positivity, and the ongoing presence of the bacteria over time was dependent on the species involved. Hence, culling ewes with palpable udder half defects that had more stable bacterial species could contribute to reducing the recurrence of palpable defects or mastitis.